2013
DOI: 10.1111/ajt.12199
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Renal Transplant Biopsy via a Transfemoral Approach

Abstract: Percutaneous renal biopsy (PRB) of kidney transplants might be prevented by an elevated risk of bleeding or limited access to the allograft. In the following, we describe our initial experience with 71 transvenous renal transplant biopsies in 53 consecutive patients with unexplained reduced graft function who were considered unsuitable candidates for PRB (4.2% of all renal transplant biopsies at our institution). Biopsies were performed via the ipsilateral femoral vein with a renal biopsy set designed for tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…When performing two biopsy passes, good diagnostic efficacy could be achieved with the TER approach (93.1%). In other PRTB studies, the rates of adequate samples as per Banff criteria ranged from 54.9% to 96.0% [6,13]. To date, two studies have reported higher specimen adequacy than ours [1,13].…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…When performing two biopsy passes, good diagnostic efficacy could be achieved with the TER approach (93.1%). In other PRTB studies, the rates of adequate samples as per Banff criteria ranged from 54.9% to 96.0% [6,13]. To date, two studies have reported higher specimen adequacy than ours [1,13].…”
mentioning
confidence: 63%
“…By use of Doppler ultrasound, 12 AVF were detected (4.6%) neither of which required embolization. Our complication rates can be compared to historical data in Table 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Sample adequacy could be retrospectively assessed for 156 tissue core samples.…”
mentioning
confidence: 99%
“…Intravascular ultrasound (IVUS) is already used in a range of transvenous renal and hepatic interventions …”
Section: Discussionmentioning
confidence: 99%
“…18 Intravascular ultrasound (IVUS) is already used in a range of transvenous renal and hepatic interventions. 19,20 In conclusion, provided adequate tumour volume and anatomy transvenous core biopsy may provide a safe and effective alternative to mediastinoscopic, bronchoscopic or CT guided biopsy. Procedures can be performed via the transfemoral or transjugular route.…”
Section: Future Directionsmentioning
confidence: 95%
“…Transjugular renal biopsy provides an alternative to the percutaneous route in patients with contraindications including, most commonly, bleeding diathesis [1]. The procedure has been shown to provide adequate an pathologic specimen and is associated with a complication rate on par with the traditional percutaneous method [2] [3]. Despite being well documented as a consequence of percutaneous biopsy, arteriovenous fistulas (AVFs) are relatively infrequently discussed in the context of a transvenous approach.…”
Section: Introductionmentioning
confidence: 99%